Recurrent polyploidy and descending dysploidy as plant genome shapers: Insights from Sporobolus (Chloridoideae, Poaceae) genomes - Morgane Milin; Oscar Lima; Lin-Feng Li; Bo Li; Marc Beringer; Christian Parisod; Malika Ainouche; Armel Salmon (PLoS ONE, 2026)
Polyploidization or whole genome duplication (WGD) is a source of genetic and phenotypic novelties and is a widespread mechanism of speciation across plant lineages. It is often followed by complex genome dynamics, including diploidization. Recurrent polyploidization leads to overlapping genomic processes complicating efforts to reconstruct genome histories in extant species. Here, we focused on the complex and understudied Chloridoideae subfamily of grasses, where polyploidy is recurrent and base chromosome number variation particularly common. We explored the evolutionary history of Sporobolus genomes through comparative genomics analyses, including species from sections Sporobolus and Spartina and selected representatives of different grass lineages. We used the WGD_Tracker pipeline to identify homologous genes and estimate their divergence, as well as to detect syntenic regions, and reconstruct karyotypes. We found that sections Sporobolus and Spartina diverged 13.2–26.0 million years ago (Mya), based on molecular clock analyses, and showed that the two WGD events detected in section Spartina ( S. maritimus and S. alterniflorus ) occurred independently of another WGD in section Sporobolus ( S. stapfianus and S. pyramidalis ). We also identified five nested chromosome insertions (NCI), a major descending disploidy mechanism that resulted in a new base chromosome number (n = 15) in section Spartina subsection alterniflori . The ancestral grass chromosome 12 appears particularly prone to structural modifications – such as insertions and rearrangements – throughout Chloridoideae evolution. Both ancestral chromosomes 11 and 12 were involved in a recent rearrangement that contributed to chromosome number divergence during speciation between S. alterniflorus (2n = 62) and S. maritimus (2n = 60), estimated at 3.7–7.7 Mya. Comparative analyses of Chloridoideae genomes provide new insights into genome duplication histories and post-polyploidization genome restructuring through descending dysploidy and revealed that NCIs are a prevalent diploidization mechanism, offering new perspectives to explore the genomic innovations underpinning the success of allo-polyploids.